Navigating Diversity: A Retrospective Analysis of Policies to Mitigate Ethnic and Religious Tensions in Singapore - Zhang, Zikang (International Journal of Social Sciences and Public Administration, 2024)
Singapore is a country made up of many different ethnic groups, including Chinese, Indians, Malays and minorities of Europeans and Japanese. This paper examines Singapore’s approach to managing ethnic and religious diversity, a critical challenge in a nation with a complex demographic makeup. This research explores the effectiveness of Singapore’s multifaceted policies aimed at mitigating ethnic and religious tensions, focusing on areas such as education, housing, cultural integration, and economic development. Utilizing a retrospective analysis, the study draws on secondary data sources, case studies, and policy reviews to evaluate the impact of these policies on social cohesion and harmony. The findings reveal that Singapore’s strong governmental leadership and comprehensive policy framework have been instrumental in fostering racial harmony and social stability. The study concludes that while Singapore’s model is effective, ongoing efforts are required to address emerging challenges, particularly in maintaining equity across all ethnic groups and ensuring inclusive representation in decision-making processes. This research offers valuable insights into how multicultural societies can be managed effectively, with potential lessons applicable to other nations facing similar challenges.